Penerapan Model Transportasi dan Decision Tree pada Distribusi Barang - Arlita Armanto; Haryadi Sarjono (Bina Nusantara University, 2012)
Goods distribution has a firm connection with transportation cost. Transportation method used by a company will cause great impact on company’s profit. If company’s profit can be maximal, the company will be able to develop its business even greater. Some problem solution steps proposed were: determining optimum criteria, developing alternative solution, developing optimum model, and practicing chosen implicative planning solution. These steps were implemented to obtain optimum goods distribution cost to gain maximum profit. This research resulted in that the distribution cost for goods implemented by current method in the company has been already optimum. Then for the following development, Decision Tree Method was used, where the results are: shipping to Yogyakarta using Sinar Aji transportation service with minimum EMV Rp.2.993.342; shipping to Salatiga using own car with EMV Rp.2.659.388; shipping to Purwokerto using Sinar Aji transportation service with EMV Rp.2.563.859; shipping to Cirebon using Sinar Aji transportaion service with EMV Rp.2.443.792; shipping to Semarang using Sinar Aji transportation service with EMV Rp.4.203.489. As the conclusion, goods shipping method which has been implemented by the company until now is optimum so it still can be used for any following business development as well as provides an iluustrative plan for the company.